Profil Gaya Belajar Bahasa Inggris Siswa SMA Negeri 7 Kota Padang - Havid Ardi (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2006)
This research was aimed at describing the learner's profile of SMA Negeri 7 Padang in studying English. It is aimed at: (1) identifying learning style of the students, and (2) identifying their preference related to their learning style. The research result of the study shows that most of the students were authority-oriented learners. In this case they depend on the English teachers. Furthermore, it was found that most of the students like the teachers to use Indonesian rather than English in the classroom including in giving explanation of difficult words. Then, they like the teacher to give correction. Finally, they like studying in group, and they have high internal motivation.Key words: learning style, students, motivation